The Design of the Puruk Cahu City Health Office Filing Information System - Hanafi Fajar; Esi Putri Silmina (Procedia of Engineering and Life Science, 2021)
The advancement of computerized-based information technology which is able to play an important role as a tool in archiving documents such as incoming and outgoing mail, data processing, and can help solve small problems to very complex problems or even in decision support. At the Puruk Cahu City Health Office, the archiving of incoming and outgoing letters is still manual with notes in the agenda book which makes it difficult to search for letter files. This aims to create a system for collecting incoming and outgoing mail to make it easier for mail archiving and mail search. The research method used is the method of observation, interviews, and literature study. With the integrated design of the archiving information system at the Puruk Cahu City Health Service Office, it will be able to help the performance of the Puruk Cahu City Health Office employees.